Novel intramolecular aminohydroxylation toward the syntheses of 2′-amino-2′-ethynyl nucleosides. (25th May 2021) - Huang, Yuhua; Bennett, Frank; Buevich, Alexei; Girijavallabhan, Vinay; Kerekes, Angela D.; Huang, Hsueh-Cheng; Tawa, Paul; Bogen, Stephane L.; Davies, Ian W.
Graphical abstract: Highlights: Tertiary amino nucleoside via tethered aminohydroxylation. Diastereospecificity. Nucleosides bearing ethynyl/amino at the C2′ position. Abstract: Syntheses of both 2′-amino-2′-ethynyl guanosine and uridine, using an intramolecular aminohydroxylation reaction as the key step, are described. The corresponding 5′- O -triphosphates of the aforementioned nucleosides were obtained and the inhibitory activity was subsequently evaluated against the hepatitis C virus NS5B polymerase.